Factors affecting polymerization of resin-based composites: A literature review - Maan M. AlShaafi (Elsevier, 2017)
Aim: The aim of this review was to help clinicians improve their understanding of the polymerization process for resin-based composites (RBC), the effects of different factors on the process and the way in which, when controlled, the process leads to adequately cured RBC restorations. Methods: Ten factors and their possible effects on RBC polymerization are reviewed and discussed, with some recommendations to improve that process. These factors include RBC shades, their light curing duration, increment thickness, light unit system used, cavity diameter, cavity location, light curing tip distance from the curing RBC surface, substrate through which the light is cured, filler type, and resin/oral cavity temperature. Conclusion: The results of the review will guide clinicians toward the best means of providing their patients with successfully cured RBC restorations. Keywords: Review, RBC, Polymerization